An Estimate of the Average Number of Recessive Lethal Mutations Carried by Humans. Issue 4 (18th February 2015) - Gao, Ziyue; Waggoner, Darrel; Stephens, Matthew; Ober, Carole; Przeworski, Molly
Abstract: The effects of inbreeding on human health depend critically on the number and severity of recessive, deleterious mutations carried by individuals. In humans, existing estimates of these quantities are based on comparisons between consanguineous and nonconsanguineous couples, an approach that confounds socioeconomic and genetic effects of inbreeding. To overcome this limitation, we focused on a founder population that practices a communal lifestyle, for which there is almost complete Mendelian disease ascertainment and a known pedigree. Focusing on recessive lethal diseases and simulating allele transmissions, we estimated that each haploid set of human autosomes carries on average 0.29 (95% credible interval [0.10, 0.84]) recessive alleles that lead to complete sterility or death by reproductive age when homozygous. Comparison to existing estimates in humans suggests that a substantial fraction of the total burden imposed by recessive deleterious variants is due to single mutations that lead to sterility or death between birth and reproductive age. In turn, comparison to estimates from other eukaryotes points to a surprising constancy of the average number of recessive lethal mutations across organisms with markedly different genome sizes.